TOP HITS IN IT JOB MIGRATION. (Communications of the ACM, 2007)
The article discusses a report released by the Brookings Institution about information technology jobs. The report reveals that one out of every five programming, software engineering, and data-entry jobs in Silicon Valley will be lost to offshoring by 2017. The study was created through an analysis of United States Bureau of Labor Statistics data with Forrester Research offshoring forecasts. It is expected that the San Jose area will lose approximately one quarter of information technology jobs compared to 2004 data.